Phenotype-Driven Virtual Panel Is an Effective Method to Analyze WES Data of Neurological Disease - Wang, Xu; Shen, Xiang; Fang, Fang; Ding, Chang-Hong; Zhang, Hao; Cao, Zhen-Hua; An, Dong-Yan (Frontiers in Pharmacology, 2019)
Abstract Objective Whole Exome Sequencing (WES) is an effective diagnostic method for complicated and multi-system involved rare diseases. However, annotation and analysis of the WES result, especially for single case analysis remain a challenge. Here, we introduce a method called phenotype-driven designing “virtual panel” to simplify the procedure, and assess the diagnostic rate of this method. Method WES was performed in samples of 30 patients, core phenotype of probands were then extracted and inputted into an inhouse software, “Mingjian” to calculate and generate associated gene list of virtual panel. Mingjian is a genetic diseases computer supportive diagnostic system that based on the databases of HPO, OMIM, HGMD. The virtual panel that generated by Mingjian system was then used to filter and annotate candidate mutations. Sanger sequencing and conducted co-segregation analysis among the family to confirm the filtered mutant. Result We first used phenotype-driven designing “virtual panel” to analyse the WES of a patient whose core phenotype is ataxia, seizures, esotropia, puberty and gonadal disorders, and global developmental delay. Two mutations, c.430T>C and c.640G>C in PMM2 were identified by this method. This result was also confirmed by Sanger sequencing among the family. The same method was then used in annotation of WES data of other 29 neurological rare disease patients. The diagnostic rate was 65.52%, which is significantly higher than the diagnostic rate before. Conclusion Phenotype-driven designing virtual panel could achieve low-cost individualised analysis. This method may decrease the time-cost of annotation, increase the diagnostic efficiency and the diagnostic rate Keywords WES, phenotype-driven, virtual panel, rare disease